Axial crushing of thin-walled tube with hole under quasi-static loading - AL-Dabbagh, Minah Mohammed Fareed Abd-A (2016)
Thin-walled tube is one of the energy absorbing structure utilized to dissipate energy and increase the efficiency of crashworthiness. During the accident, thin-walled tube dissipates the kinetic energy of the structure and converts it into other form of energy. Thus, this gives enough energy dissipation before hitting the human. This study examines the circular and square thin-walled tubes of mild steel subjected to axial crushing test by using Instron machine. These tubes include imperfection (round holes) located at three different locations. The theoretical results obtained from mathematical equations for the circular and square tubes crushing have been compared to the experimental results and a good agreement has been achieved between the theoretical and experimental results. The analysis of load-displacement characteristics includes the peak load, energy absorption capacity, mean crushing load, crush force efficiency (CFE), and specific energy absorption(SEA) results. The diameter, location and number of the holes were varied to investigate the effect of these parameters to the load-displacement characteristics. The location of round hole is located in 3 different level in the tube. As a result, the circular tube is capable of providing better decrease peak load and higher absorbed energy compared to the square tube.It was found that the better specimen is the circular tube with multi-hole, due to it has the excellent result in decrease the peak load reached to 16 %, it was concluded that value of the peak load is optimum in circular thin-walled tube. While the value of energy absorption slightly decreases in all specimens with holes compared with tube without hole. The location of holes in circular tube has the effect on the type of deformation. However, it does not affect the deformation in the square tube the location unaffected on the deformation. At the end, the modifications performed on the original tube shows an improvement in the load-displacement characteristics. The information obtained in this study will serve as a guide to better design the thin-walled tube in the future.